Occupational Therapy: An Essential Component of Support for Young Children With Cancer. (April 2023) - Sparrow, Jessica; Dagen, Hannah; Harris, Allison; Schwartzberg, Sarah; Weathers, Lucy; Kibby, Megan; Harman, Jennifer L.; Jacola, Lisa M.
We established a multidisciplinary early childhood clinic to support infants and toddlers receiving cancer treatment. The access to occupational therapy (OT) in this population is unknown. To describe the access to OT for infants and toddlers with cancer. We retrospectively reviewed medical records to determine the frequency and characteristics of children with cancer who were referred to OT. Demographic data, medical information, and frequency of referrals were extracted from September 2015 to September 2018. Of the 134 patients, 112 (83.6%) received an OT evaluation: 88.4% were referred for hospital-based OT services; 42.0% were recommended for services upon returning home. Between-group comparisons revealed significant differences in referrals for home- or community-based OT services based on age and disease. OT is crucial to treatment plans that address the developmental needs of young pediatric oncology patients during hospitalization and thereafter. Recommendations for monitoring this vulnerable population are provided.